Quality control of the long-distance runner of the category 14 – 15 years (Original) (Revista científica Olimpia, 2020)
The objective of this research is to make indicators for the quality control of the long-distance runner of the Integral School of Sport in Santiago de Cuba. For this paper, there were used theoretical methods: analysis-synthesis, induction-deduction; empirical: systemic-structural-functional, observation, measurement, quasi-experiment and the statistical ones: arithmetic mean (), standard deviation (S), as well as the interview technique. The importance of this research lies in the fact that it provides coaches with a different option to improve the quality of the results and expectations of current sports in the competitions of their long-distance runners. The discipline of long-distance running, since ancient times, has suffered changes in its nature, and therefore it has undergone transformations that have been characterized by different authors in the studies carried out. As an example of these, you find the patterns of African runners who have turned the final stages of their races into a spectacle. With the increasing development of athletics and the current scientific contributions, the quality control process in the preparation of long distance runners plays a fundamental role in respect to the systematic application of speed, strength and body weight indicators as a tool to achieve objectives. The present work is comprised of two stages, the first one has a sample of the entire population at the ages of 11-14 years with the objective of continuing the research in the second one with the same monitoring of the indicators, but in the last year of the school category (14 - 16).
Keywords: corridor; quality; control; preparation